2011
DOI: 10.1007/s10509-011-0904-6
|View full text |Cite
|
Sign up to set email alerts
|

Beam propagation and Langmuir wave generation in a plasma with κ distribution function

Abstract: Using a kappa velocity distribution function for the electrons of the background plasma, the dynamics of a beam of hot electrons streaming through the plasma and the generation of Langmuir waves are investigated in the frame work of quasilinear theory. It is shown that the Langmuir waves are strongly damped by high energy tail of the Kappa distribution function. The spatial expansion of the beam is reduced and the spectral density of Langmuir waves becomes narrower. The height of the plateau in the beam distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…New formulation of the dielectric tensor and dispersion relations have been proposed by Summers et al (1994) and Yoon (2014). Numerical simulations have shown that the increase of energetic electrons leads to an increase of the damping of the Langmuir waves (Zaheer et al 2004;Qureshi et al 2005;Mushtaq and Shah 2006;Khalilpour and Foroutan 2012). Note that not only Langmuir waves are affected by the presence of enhanced tails: the growth rate of the ion acoustic waves also decreases (Zaheer et al 2004;Arshad et al 2014), with the possible consequences on the decay of the Langmuir waves when coupling with on acoustic waves is considered.…”
Section: Theorymentioning
confidence: 99%
“…New formulation of the dielectric tensor and dispersion relations have been proposed by Summers et al (1994) and Yoon (2014). Numerical simulations have shown that the increase of energetic electrons leads to an increase of the damping of the Langmuir waves (Zaheer et al 2004;Qureshi et al 2005;Mushtaq and Shah 2006;Khalilpour and Foroutan 2012). Note that not only Langmuir waves are affected by the presence of enhanced tails: the growth rate of the ion acoustic waves also decreases (Zaheer et al 2004;Arshad et al 2014), with the possible consequences on the decay of the Langmuir waves when coupling with on acoustic waves is considered.…”
Section: Theorymentioning
confidence: 99%
“…This approach is called quasi-gas-dynamical or shortly gas-dynamical description of the quasi-linear system. In the gas-dynamic description, it is assumed that the beam distribution is always in a plateaued state and characterized by its height and upper boundary in velocity space (Foroutan et al 2005(Foroutan et al , 2007a(Foroutan et al ,b, 2008Khalilpour et al 2009;Khalilpour and Foroutan 2011).…”
Section: Introductionmentioning
confidence: 99%